Rice husk biochar effects on ammonia volatilization during poultry litter aerobic composting - Alarefee, Hamed Ahmed; Ishak, Che Fauziah; Othman, Radziah; Karam Singh, Daljit Singh (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Poultry litter (PL) provides important nutrients and organic matter. However, inappropriate treatment can cause environmental problem by increasing global warming. Co-composting PL with rice husk biochar (RHB) is a good technique to reduce gas emission and improve quality of compost produced due to the ability of biochar to absorb ammonia gas and ammonium during composting. A study was conducted to evaluate the effect of blending PL with RHB mixtures at different C/N ratio on ammonia (NH3) volatilization. Four PL+RHB ratio was composted in ratio of 0:1, 0.5:1, 1.3:1 and 2.5:1 PL: RHB ratio on dry weight, proportion of RHB was 0, 33.33, 56.53 and 71.4 % to achieve the suitable C/N ratio of about 15, 20, 25, and 30 respectively. The NH3 was measured throughout the period of composting under constant aeration system. The results showed that addition of RHB to PL could accelerate the organic matter degradation and shorten the thermophilic phase compared PL compost without RHB. Depending on the C/N ratio, cumulative NH3 emission was significantly reduced by 78.15, 94.89 and 97.96% relative to control (C/N ratio 15:1) for 20:1, 25:1 and 30:1 respectively. In addition, co-composting PL with RHB at C/N ratio of 20:1, 25:1 and 30:1 C/N ratio respectively could reduce the nitrogen loss by 40.12, 59.40 and 12.96% compared to control. Ammonia lost expressed as percent of total nitrogen (TN) were 40.28, 20.93, 12.29 and 2.90% for C/N ratio 15, 20, 30, and 35, respectively. TN retained was 75.96, 85.61, 90.24 and 79.10% respectively for C/N ratio 15, 20, 30, and 35 at the end of composting (as a percentage of initial TN) N emitted as ammonia based on the percentage of initial N was significantly lower (P≤0.05) by 67.60, 87.56 and 93.52% for the biochar treatment composts, compared to the control. N loss as percentage based of initial TN 24.04, 14.39, 9.76 and 20.92% for C/N ratio respectively. Blending Rice husk biochar with poultry litter at different C/N ratio can reduce NH3 volatilization and also reduce overall operational costs of waste disposal by reducing the composting time with nitrogen conservation and carbon sequestration.